2021
DOI: 10.1002/htj.22142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multislip and distinct heat source on MHD Carreau nanofluid flow past an elongating cylinder using the statistical method

Abstract: This study focuses on studying the impact of multiple slip effects on the hydromagnetic Carreau nanofluid flow over an elongating cylinder considering a linear heat source and exponential space‐based heat source. Suitable transformations are used in converting the highly nonlinear system of partial differential equations governing the flow into a system of ordinary differential equations and hence resolved using the Runge–Kutta method of order four coupled with the shooting method. BVP5C and RKF45 are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The validation of the numerical technique has been adjudged through restrictive studies of Khan and Pop [43] and Wang [44] (displayed in Table 1). For stronger validation, the skin friction coefficient has been compared with the work of Sabu et al [40] (see Table 2).…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The validation of the numerical technique has been adjudged through restrictive studies of Khan and Pop [43] and Wang [44] (displayed in Table 1). For stronger validation, the skin friction coefficient has been compared with the work of Sabu et al [40] (see Table 2).…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…The governing equations [23, 24, 33, 40] are given by: ()ruxbadbreak+()rvrgoodbreak=0$$\begin{equation}\frac{{\partial \left( {ru} \right)}}{{\partial x}} + \ \frac{{\partial \left( {rv} \right)}}{{\partial r}} = 0\ \end{equation}$$ uux+vur=ϑfrur()1+Γ2ur2n12+ϑf2ur2()1+Γ2ur2n12+ϑfn1normalΓ22ur2()ur2()1+Γ2ur2n32σfB02uρf$$\begin{eqnarray} u\frac{{\partial u}}{{\partial x}} + v \frac{{\partial u}}{{\partial r}} &=& \frac{{{\vartheta }_f}}{r}\ \frac{{\partial u}}{{\partial r}}{\left( {1 + {{{\Gamma}}}^2{{\left( {\frac{{\partial u}}{{\partial r}}} \right)}}^2} \right)}^{\frac{{n - 1}}{2}} + {\vartheta }_f\frac{{{\partial }^2u}}{{\partial {r}^2}}{\left( {1 + {{{\Gamma}}}^2{{\left( {\frac{{\partial u}}{{\partial r}}} \right)}}^2} \right)}^{\frac{{n - 1}}{2}}\nonumber\\ && + \ {\vartheta }_f\...…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The pertinent flow parameters are taken as the independent variables and physical quantities (like, drag coefficient, mass transfer rate, or heat transfer rate) are chosen as the dependent variable. Studies utilizing statistical approaches can be found in References [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%